The Effect of Different Mixing Methods on the Properties of Calcium-enriched Mixture Cement: A Systematic Review of in Vitro Studies - Samiei, Mohammad; Shirazi, Sajjad; Pournaghi Azar, Fatemeh; Fathifar, Zahra; Ghojazadeh, Morteza; Alipour, Mahdieh (Iranian Endodontic Journal, 2019)
Introduction: It has been shown that the mechanical and physical properties of Calcium Enriched Mixture (CEM) cement are influenced by the mixing methods. Despite several studies conducted on different mixing methods of CEM cement, there is no systematic review to summarize the results. This systematic review was conducted to investigate the effect of different mixing techniques on mechanical and physical characteristics of CEM cement. Methods and Materials: A professional librarian with skills in informatics conducted a systematic search by searching electronic databases PubMed/MEDLINE and Scopus and Ovid for English language peer-reviewed articles published between 1992 and April 2019. Results: Initial searches from all sources identified 1175 references. Two of the authors examined the titles, abstracts of these articles and the full reports of 20 studies were obtained, and data extraction was performed. Seven studies satisfied the eligibility criteria for the review. The effect of different mixing methods was investigated on bacterial microleakage, push-out bond strength, flow rate, compressive strength, solubility, pH, film thickness, dimensional changes, working time, setting time and quality of the apical plug. Conclusion: Based on the results of this systematic review, some of the important properties of CEM cement were affected by different mixing methods. Although none of these mixing methods could improve all the properties, mechanical and manual methods were more effective compared to ultrasonic method. Keywords: Calcium-enriched Mixture Cement; Systematic Review; Ultrasonic